GENRE AND COMPOSITIONAL PECULIARITIES OF THE PLAY “PATHETIC SONATA” BY MYKOLA KULISH - Vasyliuk, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article has analyzed the play “Pathetic Sonata” by Mykola Kulish, it sgenre and compositional peculiarities. It is indicated that the writer has revived the traditions of the ancient Ukrainian drama of crib. Events in the work occurinthebasement, in the atticandontwofloors of the house simultaneously. The play is written as a memory-monologue, the refore it provides for attraction of epic means. There marks are close to lyrical reflections. Lyricism deepens due to musical elements. It is proved that the artist uses elements of “the theater of the absurd”.